Myocarditis and inflammatory cardiomyopathy: from diagnosis to treatment - Felicitas Escher; Carsten Tschoepe; Dirk Lassner; Heinz-Peter Schultheiss (KARE Publishing, 2015)
Based on the definition in the European Society of Cardiology statement, myocarditis is an inflammatory disease of the myocardium diagnosed by established histological, immunological, and immunohistochemical criteria, whereas inflammatory cardiomyopathy is myocarditis in association with cardiac dysfunction. Actual incidences of myocarditis and CMi are difficult to determine. Studies addressing the issue of sudden cardiac death in young people report a highly variable autopsy prevalence of myocarditis, ranging from 2-42% of cases. Similarly, biopsy-proven myocarditis has been reported in 9-16% of adult patients with unexplained nonischemic dilated cardiomyopathy (DCM). In up to 30% of cases, biopsy-proven myocarditis can progress to DCM and is associated with a poor prognosis. Prognosis in myocarditis patients also varies according to underlying etiology.